Rickettsiae in questing Ixodes ricinus ticks in the Czech Republic - Venclikova, Kristyna; Rudolf, Ivo; Mendel, Jan; Betasova, Lenka; Hubalek, Zdenek (Ticks and tick-borne diseases, 2014)
Tick-borne rickettsiae are an important topic in the field of emerging infectious diseases. In the study, we screened a total of 1473 field-collected Ixodes ricinus ticks (1294 nymphs, 99 males, and 80 females) for the presence of human pathogenic rickettsiae (Rickettsia helvetica, R. monacensis, 'Candidatus Neoehrlichia mikurensis', and Anaplasma phagocytophilum) in natural and urban ecosystems using molecular techniques. The minimum infection rate (MIR) for Rickettsia spp. was found to be 2.9% in an urban park and 3.4% in a natural forest ecosystem; for 'Candidatus Neoehrlichia mikurensis', we observed MIRs of 0.4% in the city park and 4.4% in the natural habitat, while for A. phagocytophilum the MIR was 9.4% and 1.9%, respectively. Our study provides the first data on the occurrence of human pathogenic rickettsiae in questing I. ricinus ticks in the Czech Republic.
Keywords: Ixodes ricinus; Česká republika; Ixodes; Rickettsia spp.; Rickettsia; Czech Republic; Polymerase Chain Reaction; polymerázová řetězová reakce; klíště; Animals; ‘Candidatus Neoehrlichia mikurensis’; Anaplasma phagocytophilum; Rickettsia helvetica; zvířata; Rickettsia monacensis